Rekonsiliasi Arab Saudi dan Iran dalam Perspektif Konstruktivisme - Musofa, Ahmad Zainal (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2023)
Abstract This article describes the reconciliation between Saudi Arabia and Iran that recently occurred. This study aims to explore more deeply related to how the relationship between Saudi Arabia and Iran is post-reconciliation. Then, revealing China's interests as an actor mediating Saudi-Iran. The writer uses constructivism theory as a tool to analyze the discussion. Then the author uses a qualitative type method with a literature study approach. This research concludes that reconciliation between Saudi Arabia and Iran through Chinese mediation succeeded in reuniting the two countries which were often involved in tensions for a long time. This reconciliation also has an impact on the political constellation in the Middle East where countries in alliance with Saudi and Iran will be softer towards countries that are considered enemies. Then, China has an interest in increasing its economic sector in the Middle East such as the BRI policy, especially with Saudi-Iran. Then China expects maximum support from Middle East and North Africa (MENA) countries in international forums. Furthermore, China seeks to compete with the United States as a threat in the field of security through its presence in the Middle East as a party capable of giving hope for peace..